The clinical efficacy and safety of different biliary drainage in malignant obstructive jaundice: a meta-analysis - Wang, Yanzhao; Zhao, Xuebo; She, Yan; Kang, Qian; Chen, Xianxia (Frontiers in Oncology, 2024)
Background: Currently, percutaneous transhepatic cholangial drainage (PTCD) and endoscopic retrograde cholangiopancreatography (ERCP) are commonly employed in clinical practice to alleviate malignant obstructive jaundice (MOJ). Nevertheless, there lacks a consensus regarding the superiority of either method in terms of efficacy and safety. Aim: To conduct a systematic evaluation of the effectiveness and safety of PTCD and ERCP in treating MOJ, and to compare the therapeutic outcomes and safety profiles of these two procedures. Methods: CNKI, VIP, Wanfang, CBM, PubMed, Web of Science, Embase, The Cochrane Library, and other databases were searched for randomized controlled trials (RCTs) on the use of PTCD or ERCP for MOJ. The search period was from the establishment of the databases to July 2023. After quality assessment and data extraction from the included studies, Meta-analysis was performed using RevMan5.3 software. Results: A total of 21 RCTs involving 1,693 patients were included.